Accuracy of two different apex locators for working length determination during root canal retreatment of mandibular molars using two different retreatment files: An in vitro study - Ajay Chhabra; Ruhani Bhatia; Nisha Garg; Shruti Sharma; Aarushi Dogra; Ashu Jhamb (Wolters Kluwer Medknow Publications, 2018)
Aim: The aim of this study was to evaluate the accuracy of two different apex locators for working length determination during root canal retreatment of mandibular molars in an in vitro study. Method: Sixty extracted mandibular first molars with separate mesial canals and apical foraminae and one distal canal were selected. The mesiobuccal and distal canals were investigated; the length with the file tip at the major diameter was defined as the tooth length (TL). The canals were prepared with ProTaper files to 1 mm short of this and filled with gutta-percha and AH Plus sealer. One week later, the root fillings were removed using ProTaper and M2 retreatment files. Tooth length was remeasured and recorded as the retreatment tooth length (RTL). Then electronic measurements were taken at the major (electronic apex locator (EAL) major) and minor (EAL minor) foraminae with Root ZX and Apex ID apex locator as suggested by the instrument display. These lengths were compared with RTL and measurements 0.5 and 1 mm short of this distance. Results: For both canals, no significant difference was found between RTL and EAL major, and 0.5 mm short of RTL and EAL minor with Root ZX apex locator and protaper retreatment files. There were significant differences found between Apex ID apex locator with M2 retreatment files readings. Conclusion: Root ZX apex locator was more accurate as compared to Apex ID apex locator in determining the working length in teeth after removing the root canal obturating material.